2018
DOI: 10.1111/liv.14000
|View full text |Cite
|
Sign up to set email alerts
|

Liver decompensation in HIV/Hepatitis B coinfection in the combination antiretroviral therapy era does not seem increased compared to hepatitis B mono‐infection

Abstract: Background & Aims HIV/hepatitis B virus (HBV) coinfected subjects are thought to have faster progression to end‐stage liver disease (ESLD) than HBV mono‐infected subjects. We assessed whether this remains in the current cART‐era. Methods Data from subjects with follow‐up completion post‐2003 were compared between HIV/HBV coinfected subjects in the Dutch HIV Monitoring database and HBV mono‐infected subjects from two centres. The primary outcomes of composite ESLD included portal hypertension, decompensated cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The negative impact of HBV on the survival of HIV‐infected patients has been well demonstrated in previous studies, especially among those with higher HBV DNA load . HIV/HBV‐coinfected patients have 17 times higher risk for liver‐related mortality than those with HBV monoinfection despite effective HBV treatment . HIV coinfection worsens the natural history of HBV by accelerating the progression of HBV‐related liver diseases .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The negative impact of HBV on the survival of HIV‐infected patients has been well demonstrated in previous studies, especially among those with higher HBV DNA load . HIV/HBV‐coinfected patients have 17 times higher risk for liver‐related mortality than those with HBV monoinfection despite effective HBV treatment . HIV coinfection worsens the natural history of HBV by accelerating the progression of HBV‐related liver diseases .…”
Section: Discussionsupporting
confidence: 89%
“…TDF‐containing cART has been recommended for HIV/HBV‐coinfected patients because TDF can achieve sustained viral suppression of both lamivudine‐susceptible and lamivudine‐resistant HBV, which subsequently improves liver fibrosis . Moreover, TDF‐containing cART has superior HIV virological response and better tolerability than other regimens containing zidovudine and abacavir .…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulated that the more widespread use of HBV treatment among PLWH on ART likely accounted for this protective effect but antiviral therapy was not captured in this study. A Dutch study however did capture antiviral therapy and found no significant difference in time to ESLD or all-cause death when comparing HIV-HBV-coinfected to HBV monoinfected individuals from 2003 to 2015 [39]. The findings from this study need to be interpreted with caution due to the substantial difference in follow-up between monoinfected and coinfected cohorts (median 3.8 vs 10.3 years with attrition of 40% vs 12% respectively).…”
Section: Role Of Hbv-specific Therapy On Liver Disease Progression Inmentioning
confidence: 60%
“…Numerous studies have proven the importance of dual activity drugs for coinfection treatment. Using highly effective cART with dual activity is able to significantly reduce the risk of developing end-stage liver disease in HIV/HBV coinfected patients (12). Interruption of HIV medications with anti-HBV activity in HIV/HBV coinfected individuals may result in HBV reactivation and/or hepatitis (13).…”
Section: Investigational Drugs With Dual Activity Against Hbv and Hivmentioning
confidence: 99%